Peran Saksi Ahli Forensik dalam Proses Pembuktian Tindak Pidana Pembunuhan - Ilyas Rahman; Handar Subhandi Bakhtiar (HOKI : Journal of Islamic Family Law, 2024)
The role of autopsik expert witnesses is very important in the process of proving criminal cases, especially murder. The process of examining criminal cases in court, there must be two valid pieces of evidence as a minimum standard. In relation to murder cases, judges need autopsik experts to find out the causes of a crime. The autopsik expert's testimony in the Visum et Repetrium plays an important role in deciding a criminal case, because it contains information about the causes that are the result of murder.